E-learning theory and practice - Haythornthwaite, Caroline; Andrews, Richard 1953- (SAGE, 2011)
In 'E-learning Theory and Practice', the authors set out different perspectives on e-learning. The book deals with the social implications of e-learning, its transformative effects, and the social and technical interplay that supports and directs e-learning
Includes bibliographical references (p. [227]-254) and index
Keywords: Internet in education; Computer-assisted instruction; Web-based instruction / Social aspects; Gesellschaft; E-Learning